2020
DOI: 10.1029/2020gl087956
|View full text |Cite
|
Sign up to set email alerts
|

Solar‐Induced Fluorescence Does Not Track Photosynthetic Carbon Assimilation Following Induced Stomatal Closure

Abstract: Since 2006, six satellites measuring solar‐induced chlorophyll fluorescence (SIF) have been launched to better constrain terrestrial gross primary productivity (GPP). The promise of the SIF signal as a proxy for photosynthesis with a strong relationship to GPP has been widely cited in carbon cycling studies. However, chlorophyll fluorescence originates from dynamic energy partitioning at the leaf level and does not exhibit a uniformly linear relationship with photosynthesis at finer scales. We induced stomatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
87
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(91 citation statements)
references
References 51 publications
(74 reference statements)
0
87
1
3
Order By: Relevance
“…The third recent study (Marrs et al, 2020) used a controlled experiment to test the relationship between fluorescence (PAM and SIF), stomatal conductance, and net photosynthesis. Marrs and colleagues induced stomatal closure (through pressure cuffs and abscisic acid) over a short time period (1 day) to show that no changes in steady‐state chlorophyll fluorescence or SIF were observed while clear reductions in stomatal conductance and carbon assimilation occurred.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The third recent study (Marrs et al, 2020) used a controlled experiment to test the relationship between fluorescence (PAM and SIF), stomatal conductance, and net photosynthesis. Marrs and colleagues induced stomatal closure (through pressure cuffs and abscisic acid) over a short time period (1 day) to show that no changes in steady‐state chlorophyll fluorescence or SIF were observed while clear reductions in stomatal conductance and carbon assimilation occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Over longer time scales, and especially those observed from space (temporal frequency >1 week), it is likely that the relationship between electron transport rate (Step 1) and carbon assimilation (Step 2) will be similar (Genty et al, 1989); however, more research along these lines is warranted, particularly under severe water and temperature stress. Notably, the Marrs et al (2020) paper suggests that the observed linear relationship between SIF and GPP at increasing scales is likely due to their common drivers: light absorbed by chlorophyll molecules and photochemical regulation. Understanding these scaling nuances are thus crucial for interpreting satellite measurements of SIF and its relationship to GPP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This equation adopts the hyperbolic light‐response‐curve used in DT but substitutes the global radiation ( R g ) with SIF, where a and b are empirical parameters to be fitted. This formulation has the flexibility to characterize both the linear and nonlinear SIF‐GPP patterns reported in literature (Li et al., 2018; Marrs et al., 2020; Y.Zhang et al., 2016; Sun et al., 2017). The nonlinearity usually occurs at short time scales (e.g., subdaily, when PAR dominates the co‐variations of SIF and GPP) and/or under stress, modulated by physiological factors, such as q L , NPQ, and/or CO 2 availability in the vicinity of Rubisco (Gu et al., 2019b).…”
Section: Methods and Datasetsmentioning
confidence: 99%